2015
DOI: 10.1002/cmdc.201500183
|View full text |Cite
|
Sign up to set email alerts
|

Bisamidate Prodrugs of 2‐Substituted 9‐[2‐(Phosphonomethoxy)ethyl]adenine (PMEA, adefovir) as Selective Inhibitors of Adenylate Cyclase Toxin from Bordetella pertussis

Abstract: Novel small-molecule agents to treat Bordetella pertussis infections are highly desirable, as pertussis (whooping cough) remains a serious health threat worldwide. In this study, a series of 2-substituted derivatives of 9-[2-(phosphonomethoxy)ethyl]adenine (PMEA, adefovir), in their isopropyl ester bis(L-phenylalanine) prodrug form, were designed and synthesized as potent inhibitors of adenylate cyclase toxin (ACT) isolated from B. pertussis. The series consists of PMEA analogues bearing either a linear or bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 58 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…Analytical TLC was performed on plates of Kieselgel 60 F 254 from Merck. NMR spectra were recorded on Bruker Avance 400 spectrometer ( 1 H at 400 MHz, 13 C at 100.6 MHz, 31 P at 161.9 MHz) with TMS or dioxane (3.75 ppm for 1 H, 67.19…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical TLC was performed on plates of Kieselgel 60 F 254 from Merck. NMR spectra were recorded on Bruker Avance 400 spectrometer ( 1 H at 400 MHz, 13 C at 100.6 MHz, 31 P at 161.9 MHz) with TMS or dioxane (3.75 ppm for 1 H, 67.19…”
Section: Methodsmentioning
confidence: 99%
“…10 ppm for 13 C NMR) as internal standard or referenced to the residual solvent signal. Mass spectra were measured on UPLC-MS (Waters SQD-2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34,35 In our SAR-study, the ethyl ester of the natural amino acid, L-phenylalanine, was selected to mask both phosphonate groups of our inhibitors. 36,37 This type of prodrug is more stable than ester prodrugs. In solution no hydrolysis was observed at pH 7.…”
Section: Chemistrymentioning
confidence: 99%
“…[19] Furthermore, 2-substituted PMEA derivatives proved to inhibit B. pertussis ACT, with promising selectivity for ACT over mammalian ACs and no cytotoxicity. [20] It was also shown that cell-permeable bisamidate prodrugs of PMEA bearing bis( l -phenylalanine isopropyl ester) moiety and its 2-substituted derivatives inhibited ACT effectively in cellular models. Although these bisamidate prodrugs did not inhibit ACT in vitro as effectively as bis(POM)PMEA, they were significantly less cytotoxic and showed better plasma stability profiles.…”
Section: Introductionmentioning
confidence: 99%